Characteristics of Professional Burnout of Oncologists - T. S. Klimenko (Креативная хирургия и онкология, 2023)
Introduction. The present paper considers the issue of emotional burnout among doctors of oncology departments. The profession of a doctor refers to so-called socionomic professions, which are associated with higher socio-psychological requirements as well as mental and psycho-emotional stress.   The relevance of the study stems from the persistent psycho-emotional problems that arise in the process of professional activity of oncologists.   Aim. To study theoretical aspects of professional burnout, to carry out experimental evaluation of professional burnout among oncologists and to develop the preventive measures contributing to reduction in symptoms of emotional burnout in oncologists.   Materials and methods. The author conducted an experimental study of the emotional burnout among oncologists and explored the diagnostics aspects of emotional burnout. The experiment was carried out by means of the questionnaire “Diagnostics of the level of emotional burnout” (V. V. Boyko). The study sample consisted of 50 oncologists.   Results and discussion. The author revealed that the symptom “experiencing psychotraumatic circumstances” is highly expressed at the stress stage in the group of oncologists with developed emotional burnout (24, 58). The symptom shows preventive reaction to the influencing aspects for emotional burnout: “emotional response” (24, 6), “reduced job performance” (31, 66), characterizing the methods of mental support; the “emotional defi cit” (25, 33), “emotional detachment” (28,12), reflecting the state of parasympathetic nervous system, are considered as the main symptom at the overstrain stage. It was found that the work with critically ill patients demands high level of professional competence, considering the increased responsibility and constant emotional stress.   Conclusion. The results of the study confi rm the presence of leading symptoms in developing emotional burnout. In order to prevent the development of emotional burnout syndrome, the author proposes to introduce psychological training programs on various topics in medical institutions to minimize professional burnout and to develop soft skills, including self-regulation in communication.